Clustering of X-Ray-Selected AGN - N. Cappelluti; V. Allevato; A. Finoguenov (Advances in Astronomy)
The study of the angular and spatial structure of the X-ray sky has been under investigation since the times of the Einstein X-ray Observatory. This topic has fascinated more than two generations of scientists and slowly unveiled an unexpected scenario regarding the consequences of the angular and spatial distribution of X-ray sources. It was first established from the clustering of sources making the CXB that the source spatial distribution resembles that of optical QSO. It then became evident that the distribution of X-ray AGN in the Universe was strongly reflecting that of Dark Matter. In particular, one of the key results is that X-ray AGNs are hosted by dark matter halos of mass similar to that of galaxy groups. This result, together with model predictions, has lead to the hypothesis that galaxy mergers may constitute the main AGN-triggering mechanism. However, detailed analysis of observational data, acquired with modern telescopes, and the use of the new halo occupation formalism has revealed that the triggering of an AGN could also be attributed to phenomena-like tidal disruption or disk instability and to galaxy evolution. This paper reviews results from 1988 to 2011 in the field of X-ray-selected AGN clustering.